Assessment of the Concretes Mechanical Strengths from the Construction Elements Supposed on Dissolving - Levigation Corrosion. (2016) - Diaconu, Livia Ingrid; Plian, Diana
Abstract: The proposed acceleration method represents a valuable work instrument that allows the obtaining of a great results volume in an acceptable time, taking into account that in exploitation, the buildings that are subjected to this type of corrosion are presenting visible degradations after a longer time. The realized device has been shown to be reliable and allows the testing of some series of 24 samples, so at the end of the experimental program, the obtained data after the results interpretation gave a clear image on the modification that are appearing in time in the concrete's structure subjected on dissolving – levigation corrosion.